EXPERT METHOD OF MANAGING THE DIDACTIC KNOWLEDGE BASE IN THE COMPUTER LEARNING SYSTEM - Шибицький, В. П.; Ісак, А. І. (Proceedings of National Aviation University (archive), 2021)
An expert method of managing the didactic knowledge base of the computer system of operator training is proposed. The dynamics of the process of declaring knowledge by the system, the model of assimilation and storage of knowledge by the operator are considered.